Phytochemicals for Breast Cancer Therapy: Current Status and Future Implications - Akhtar Siddiqui, Jawed; Singh, Aru; Chagtoo, Megha; Singh, Nidhi; Madhav Godbole, Madan; Chakravarti, Bandana (Current Cancer Drug Targets, 2015)
Breast cancer is one of the most common malignancies among women, representing nearly 30% of newly diagnosed cancers every year. Till date, various therapeutic interventions, including surgery, chemotherapy, hormonal therapy, and radiotherapy are available and are known to cause a significant decline in the overall mortality rate. However, therapeutic resistance, recurrence and lack of treatment in metastasis are the major challenges that need to be addressed. Increasing evidence suggests the presence of cancer stem cells (CSCs) in heterogeneous population of breast tumors capable of selfrenewal and differentiation and is considered to be responsible for drug resistance and recurrence. Therefore, compound that can target both differentiated cancer cells, as well as CSCs, may provide a better treatment strategy. Due to safe nature of dietary agents and health products, investigators are introducing them into clinical trials in place of chemotherapeutic agents.This current review focuses on phytochemicals, mainly flavonoids that are in use for breast cancer therapy in preclinical phase. As phytochemicals have several advantages in breast cancer and cancer stem cells, new synthetic series for breast cancer therapy from analogues of most potent natural molecule can be developed via rational drug design approach.
Keywords: phytochemicals